Criteria to facilitate the implementation of woman-centred care in childbirth units of Limpopo Province, South Africa (Part 2) - Maria S. Maputle; Donavon C. Hiss (AOSIS, 2013)
Background: Facilitation of mutual participation, respectful and egalitarian relationship between the mother and the midwife during childbirth is a critical aspect. This article delineated the criteria that would facilitate the implementation of woman-centred care in childbirth units of the Limpopo Province in South Africa, following a concept analysis described in Part 1. Empirical referents or indicators were used to measure the concept woman-centred care and to validate its existence in reality. These empirical referents were referred to as measurable properties that further verified the concept. Objective: The objective of this article was to formulate criteria that would facilitate implementation of woman-centred care in childbirth units of Limpopo Province in South Africa. Method: Criteria to facilitate the implementation of woman-centred care were formulated by the gathering of information about the topic under review and the use of resources to define the key elements of the criteria which were integrated into the Batho Pele principles. The criteria were then validated by selecting with a vested interest in the successful development and implementation of the criteria. Results: Criteria were formulated to facilitate the implementation of woman-centred care that was integrated within the framework of Batho Pele principles. Conclusion: These formulated criteria for woman-centred care will be used as an institutional self-evaluation tool to enhance implementation of the Batho Pele principles in childbirth units. These criteria will give direction and provide guidelines for the performance of midwifery staff and will also help supervisors to guide staff to improve performance.